Systematic preoperative approach for bariatric surgery, perioperative results, and economic impact - Iolanda Freire-Moreira; Maria Pilar Sanchez-Conde; Maria Pilar Sanchez-Conde; Gilles Barreira-de Sousa; Maria Isabel Garrido-Gallego; José María Rodríguez-López; Raúl Juárez-Vela; Juan Alonso Bragado; Marta Carretero-Hernández; Carlos Ricardo Vargas-Chiarella; Jesús Calderón-Moreno; María Fernanda Lorenzo-Gómez; et al. (Frontiers Media S.A., 2024)
IntroductionObesity is a complex systemic condition, involving numerous anatomical and metabolic changes. Therefore, a comprehensive preoperative assessment is essential for each patient contemplating bariatric surgery.ObjetiveThis study presents the findings of a proposed protocol designed to streamline the pre-anesthesia consultation process. Our aim was to compare the efficiency and costs of consultations guided by the protocol with those conducted without a specific strategy. The secondary outcomes assessed included postoperative (PO) length of hospital stay and surgical duration.Matherial and methodsWe conducted a retrospective cross-sectional analysis involving 206 clinical cases. Statistical analyses, including the chi-squared test, Student's t-test, and Mann-Whitney U test, were utilized based on the type of variables.ResultsThe results showed a significant reduction in the costs, pre-anesthesia consultation duration, time spent in the recovery unit, and the need for referrals. However, no statistically significant differences were observed in the delay before surgery and length of hospital stays, measured in days.ConclusionThis algorithm offers a promising approach for optimizing perioperative management in bariatric surgery, demonstrating its effectiveness in cutting costs and reducing the need for referrals.